2022
DOI: 10.1038/s41598-022-10855-z
|View full text |Cite
|
Sign up to set email alerts
|

Using virtual global landmark to improve incidental spatial learning

Abstract: To reduce the decline of spatial cognitive skills caused by the increasing use of automated GPS navigation, the virtual global landmark (VGL) system is proposed to help people naturally improve their sense of direction. Designed to accompany a heads-up navigation system, VGL system constantly displays silhouette of global landmarks in the navigator’s vision as a notable frame of reference. This study exams how VGL system impacts incidental spatial learning, i.e., subconscious spatial knowledge acquisition. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
1
3
0
Order By: Relevance
“…The greater pointing accuracy that resulted in the Cues-on condition compared to the Cues-off condition suggests that together, this set of simulated AR cues facilitated the acquisition of survey spatial knowledge of the city environment. These results replicate and extend prior work that found virtual cues to be effective landmarks (Bolton et al, 2015;Brunyé et al, 2016;Liu et al, 2022). We also found that pointing accuracy was best when pointing from home to the targets as compared to targets to home.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The greater pointing accuracy that resulted in the Cues-on condition compared to the Cues-off condition suggests that together, this set of simulated AR cues facilitated the acquisition of survey spatial knowledge of the city environment. These results replicate and extend prior work that found virtual cues to be effective landmarks (Bolton et al, 2015;Brunyé et al, 2016;Liu et al, 2022). We also found that pointing accuracy was best when pointing from home to the targets as compared to targets to home.…”
Section: Discussionsupporting
confidence: 90%
“…Others have manipulated the presence of global and local landmarks in virtual environments displayed on a large projection screen and showed that both types of landmarks were used to make route decisions, but that individuals relied on them differently when the cues were put in conflict with each other (Steck and Mallot, 2000). Recently, Liu et al (2022) also developed a "virtual global landmark (VGL)" system that constantly displayed a global landmark through a head-worn AR system during navigation. They found better incidental spatial learning with the VGL system as assessed by a map drawing task when compared to a control (auditory instruction only) condition.…”
Section: Cues In Virtual Navigationmentioning
confidence: 99%
“…The inclusion of landmarks in mobile maps for pedestrian navigation has been proposed to counter the negative effects of using GPS-based navigation systems on users' spatial learning (Raubal and Winter, 2002;Duckham et al, 2010;Liu et al, 2022). Indeed, Wunderlich and Gramann, (2021) showed that pedestrian navigation assistance that presents landmarks at intersections with verbal directions improved navigators' spatial knowledge acquisition compared to standard navigation instructions in mobile applications that communicate turn-by-turn directions using metric distance information (e.g., "turn right in 200 m").…”
Section: Landmarks and Navigationmentioning
confidence: 99%
“…Further, as the behaviour and emotional control centre of our brains, the frontal lobes are important for voluntary movement and for managing higher-level executive functions [57]. Especially, based on our previous studies [58,59], the frontal and parietal areas are found to be associated to the quality of spatial learning caused by the stimulus of VGLs and local landmarks. These two areas are also revealed by studies for their roles to reflect the spatial attention and navigation strategies [60][61][62].…”
Section: Visualizing the Eeg Datasetmentioning
confidence: 99%